Implementação da pedagogia histórico-crítica na educação do campo de municípios baianos por meio da Ação Escola da Terra: contradições e possibilidades - Santos, Manoel Gonçalves dos (Universidade Federal de São Carlos, 2020)
The present study has as its object an interface between the continuing education course made available in UFBA, through the Earth School Action (Ação Escola da Terra), to rural teachers from Bahia cities, a critical historical pedagogy and the factual teaching contexts where these educators preside. With the research, we aim to analyze the limits and possibilities resulted of this course execution for an effective implementation of CHP in the socio-educational context from cities that joined the Action. The working hypothesis, verified and confirmed in the thesis, based on the assumption that the continuing education course studied, due to its reference in the a critical historical pedagogical theory, which has a counter-hegemonic feature, constitutes a feasible way to produce a critical and qualified teacher training in rural schools, and, consequently, of inserting this pedagogical aspect in the context of these teachers' professional performance, conscious of the elements that compose the objective reality of the affected educational contexts are dribbled, which reverberates the contradictions inherent to a society ruled by capital – whose main characteristic is the capital-labor contradiction – where we can see a strong influence of pedagogical theories aligned with the neoliberal capitalist ideology, in addition to lacking in teachers' training and valuation and in the infrastructure and material of rural schools. The thesis was anchored in dialectical and historical materialist method, to produce its theoretical and conceptual framework, and to enlighten data collection and analys, which were derived from documents consulting that standardize rural education in five envolved cities (political-pedagogical project, Municipal Education Plans and Teaching Career Plans), as well as conducting interview with pedagogical advisers, secretaries of education representatives and with the teachers' union from these cities, in addition to a questionnaire application with graduated from the third edition course, concluded in 2017. We came to the conclusion that the Earth School Action at UFBA demonstrated an essential possibility, by creating an implementation of a critical historical pedagogy in the rural education from Bahia cities, with direct effects on the constitution of political competence and technique of these teachers in training course and as a result of the pedagogical work conducted by them, despite the course operational limitations and typical contradictions of the capitalist social context in which the continuing education experience and its pedagogical practices took place, in which, inexorably, has contestation, as expressed in data analysis related to working conditions, training and financial valuation of the teachers involved, indicating that a full and generalized implementation of this pedagogical theory in teacher training and school education is conditioned to the more general struggle for overcoming the capitalist mode of production.
Implementation of historical-critical pedagogy in rural education in Bahia cities through the Earth School Action: contradictions and possibilities
Keywords: Ação Escola da Terra; Implementação da pedagogia histórico-crítica; Formação continuada; The Earth School Action; Implementation of critical historical pedagogy; Continuing education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO